DEVELOPMENT OF NOVEL ALGORITHMS AND ARCHITECTURE FOR A ROBOT BASED AGRICULTURAL IMPLEMENT (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper presents novel algorithms and architecture for a Robot based agricultural implement. The application is for tilling the agricultural field. The hardware consists of a platform with four wheels and a mechanism to facilitate the forward, reverse and lateral movement of the wheels. The platform also houses a turn table, a lift and a plough. Various user defined inputs may be programmed such as length and breadth of the field, spacing between two till lines and depth of tilling. Thereafter, the entire tilling operation of the field is automated. The Robot based vehicle begins the operation from the top left corner and moves towards right tilling the field as it moves forward. Once the required length of field is reached, the vehicle halts and moves to the next row for a specified spacing between tilled rows. The movement from one row to another is in a lateral fashion by rotating the Robotic vehicle wheels by 90 degrees. No tilling is carried out till the next row is reached. The tilling operation is resumed by rotating the plough by 180 degrees and moving the vehicle in the reverse direction. This process continues till the end of the field, covering the entire breadth and maintaining the desired spacing and depth. This automated tilling requires the development of novel algorithms and an optimized architecture, which is presented in this paper. The system is user friendly and upgradable. The entire system has been realized using Verilog and is RTL compliant. The design is both platform and technology independent. The design has been simulated using ModelSim.